Technical report: a study of the SIR model for spread of dengue fever disease / Nur Farah Amirah Mohd Azizan, Nur Amirah Othman and Nor Suliha Buqia Mohd Salleh - Mohd Azizan, Nur Farah Amirah; Othman, Nur Amirah; Mohd Salleh, Nor Suliha Buqia (2016)
Various mathematical model has been used to investigate dengue transmission. The SIR model for dengue disease transmission is discussed here. In this paper, we study the SIR model which includes Susceptible which is the number of susceptible person, Infected which is the number of infected people and Removed which is the number of recovered people. Our interest here is to derive. apply and predict the transmission of SIR model. We: will investigate the transmission of the dengue viruses between the human population and the mosquitoes population in Malaysia and the result we got by using maple software. By using Maple we use the technique of dissolve to get the graph, The aim for our project to measure. and control the number of infected people by predict the cases using Maple software. In order to reduce the Dengue Haemorraghic Function (DHF) patients and to keep the number of patients at an acceptable level by the prediction the cases. We also using the data from Kementerian Kesihatan Malaysia for the year 2005 until 2014.